Radical deoxygenation of 3-azatricyclo[2.2.1.0(2,6)]heptan-5-ols to 1,2-dihydropyridines - Hodgson, D; Jones, M; Maxwell, C; Ichihara, O; Matthews, I (2005)
Radical deoxygenations of 7-alkyl-1-tosyl-3-azatricyclo[2.2.1.0 2,6]heptan-5-ols 9 (R = alkyl) give 7-alkyl-4-tosyl-2-azabicyclo[2.2. 1]hept-5-enes 10, whereas 7-aryl-1-tosyl-3-azatricyclo[2.2.1.0 2,6]heptan-5-ols 9 (R = aryl) give 2-aryl-5-tosyl-1,2- dihydropyridines 12.